The cypriot blunt-nosed viper Macrovipera lebetinus lebetinus: complete mitochondrial genome revealed by next-generation sequencing - Stephan Siegert; Joel Fonseca Nogueira; Daniel Jestrzemski; Mike Reich; Bertram Brenig (Mitochondrial DNA. Part B. Resources)
Macrovipera lebetinus lebetinus is the sole venomous snake species endemic to Cyprus, with its population declining due to habitat loss and persecution. The taxonomic status of this species remains uncertain, and there is a significant gap in available genetic information. Here, we present the first complete mitochondrial genome of M. lebetinus lebetinus, obtained from two specimens. The mitogenomes (17,151 bp and 17,152 bp) include the standard 37 genes—13 protein-coding genes, 22 tRNAs, and 2 rRNAs—as well as two control regions. Comparative analysis reveals a conserved gene order typical for Viperidae but also an unprecedented structural modification: the complete loss of the D-arm in tRNA-Cys, a feature previously unreported in snakes. Phylogenetic analysis confirms the monophyly of M. lebetinus lebetinus and M. lebetinus schweizeri. These findings contribute essential genetic data for this under-documented species, providing valuable molecular markers for future phylogenetic and conservation studies.